Desafio de cuidadores familiares no contexto da internação domiciliar - Brondani, Cecília Maria (2008)
This study aimed to describe and analyze experiences of chronic patients family carers in home stay, as well as to discuss the importance of such experiences to nursing care. It is a qualitative research developed in the Service of Home Health Care of Santa Maria s University Hospital (SIDHUSM), to which contributed 15 chronic patients family carers. This study made use of creative and sensitive method (MCS) by Cabral (1998) and the dynamics of creativity and sensitivity: Life Line, Body-Knowledge and Almanac. Data were analyzed by using some of the theoretical concepts of Discourse Analysis by Orlandi (2002). Thus, it was possible to structure two analytical categories: the first is related to the experience of being a family carer in the context of home care, which was developed in the themes: the care as an experience inherent to human beings; the experience of taking care in a disease situation; the learning with the experience of being a carer; the implications in the experience of being a carer and the home health care as a support in the care of patients in their homes. The second category is about the strategies used by carers in the care of their familiars, which was developed in the themes: the expressivity in the care; the concern with the environment and the importance of the social net support. The results pointed to the necessity of valuing the care activities developed by home carers and the built of a formal and informal net of support and help to family carers. In regard to the formal net of support, one highlighted the home care as a modality of humanizing and innovating attention which aims to invert health professionals logic of action. The moment that health professional group goes to patient s home, a space to a relation of trust and mutual help is opened allowing the construction of new knowledge.